EFFECTS OF NEW HIGH-YIELDING VARIETIES AND FERTILIZER DOSES ON THE GROWTH AND YIELD OF UPLAND RICE CROPS ON DRY LAND IN MALUKU, INDONESIA - Wahid1, La Karimuna2*, Asmin1, Sheny S Kaihatu3, Risma Fira Suneth3, Baharudin1, Imran3, Musyadik4, and Bungati5, (Chelonian Research Foundation, 2023)
The purpose of the study was to determine the effect of varieties and fertilizer doses on the growth and production of upland rice on dry land in Maluku. The study used a Split Plot Design with 25 treatment combinations and three repetitions. The treatment consists of the Main Plot, a new high-yielding variety, consisting of five levels, namely Inpago 8; Inpago 11; Inpago 12; Rindang 1 and Rintang 2, and subplot are fertilization recommendations, consisting of five levels, namely F1 = 100 kg Urea ha-1 (Farmer 1); F2 = 150 kg Urea/ha farmer 2; F3 = 100 kg Urea + 200 kg NPK ha-1; F4 = 150 kg Urea + 250 kg NPK ha-1; F5 = 1/2 F3 + liquid organic fertilizer (LOF) Compost. From two factors, 25 treatment combinations were obtained. Each combination of treatments was repeated three times, resulting in 75 experimental units. The growth and yield components modifiers were observed on determined 10 randomly sample crops per plot, while the yield of milled dry grain was observed on a sample plot of 2.0 m x 3.0 m = 6.0 m2, then converted to milled dry grain yield ha-1. Data analysis using statistical methods, consisting of analysis of variances (ANOVA) to determine the effect of treatment, and if significant, then followed by Duncan’s Multiple Range Test (DMRT) at 95 percent confidence level. The results showed that there was an interaction between new high-yielding varieties and fertilization doses on the plant height, weight of 1000 g and weight of grain filled per clump, on the contrary there was no real difference in the number of maximum tillers and productive tillers per clump, the number of filled panicles and the percentage of empty panicles per clump, panicle length, and the yield of milled dry grain (per harvest plot and ha-1). Variety of Rindang 2 with fertilizer dose of 150 kg Urea + 250 kg NPK ha-1 was the best. Inpago 8, Inpago 11, Inpago 12, Rindang 1 and Rindang 2 gave milled dry grain of uplant rice yield of 3.15 t; 2.69 t; 2.48 t; 2.22 t; and 2.08 t ha-1, respectively. The five new high-yielding varieties gave milled dry grain of upland rice between 2.08 - 3.15 t ha-1 and had no noticeable effect, so that the five varieties can be used in the intrcropping corn and upland rice planting pattern in dry land in Maluku. The treatmen of 150 kg Urea + 250 kg NPK ha-1 gave the highest yield of upland rice milled dry grain (2.91 t ha-1) but differed insignificantly compared to F3 and F5. When the recommnded fertilizer of 150 kg Urea + 250 kg NPK was not available, then fertilization recommendations of 100 kg Urea + 200 kg NPK ha-1 can be used. Keywords: New Superior Varieties, Upland Rice, NPK Fertilizer, Maluku